Evaluation of radiation protection principles observance in Iranian dental schools - GhazikhanlouSani K.; Eskandarlou A. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: In recent decades many guidelines has been conducted by radiation protection organizations about radiation protection in dentistry. This study was designed to evaluate the observance of these guidelines in educational clinics of all dental schools in Iran."nMaterials and Methods: In this cross-sectional study a questionnaire based on National Radiation Protection guidelines was conducted. The questionnaire consisted of questions about radiation protection principles in dental radiography that is needed for patients and personnel protection and quality control of radiological instruments. The questionnaires were completed by the responsible person of each radiology department of dental schools (18 schools). After gathering the data, the results were compared with radiation protection standards."nResults: There was proper condition in the case of the existence of radiation protection facilities, such as lead apron, thyroid shield and lead impacted walls. However, personnel rarely use these facilities. Usage of high speed films and existence of automatic processor in dental schools was an appreciable point. The main problem was related to the lack of regular quality control programs."nConclusion: The observance of radiation protection regulations in radiology departments of dental schools was proper. But majority of departments had no regular quality control programs; and the use of digital systems in dental radiography was not common.